Control biológico de hongos micotoxigénicos con bacterias ácido lácticas - Espinosa Salgado, Rubén (Universidad Autónoma Metropolitana, 2022)
The lost food caused by the contamination with microorganisms is an important problem to solve human survival. The contamination by fungus is a topic of great interest. because the fungus biosynthesized mycotoxins associated with several diseases. In this sense to give solutions to the problem mentioned before, in this thesis, the use of lactic acid bacteria as antagonists of the growth of Aspergillus carbonarius is proposed. The work focuses on enhancing the antifungal effect of LAB modifying the formulation of the culture medium and identifying metabolites with antifungal activity. Firstly, an analysis of the fermentation products of the LAB was carried out. The strains were characterized as homofermentative, because mainly produced lactic acid, and a low concentration of propionic acid, ethanol, and LAB strain 31 (MZ809351) also produced butyric acid. On the other hand, it was found that the highest antifungal activity occurred when the cell-free supernatant was obtained between 72 and 96 h of LAB culture under anaerobic conditions. Secondly, we analyzed the effect of the concentration of the nitrogen source and some nutritional factors. LAB strains 7 from Mexico and 31 from the Ivory Coast exhibited the highest antifungal activity, moreover, it was found that both yeast extract and ammonium citrate can be eliminated from the culture medium without affecting both growth and antifungal activity. Lastly, this part shows the antifungal activity was reduced when calcium chloride was added to culture media and was not affected by the presence of sodium chloride. The last stage corresponds to the analysis of the results of adding polyols to the MRS culture medium on the production of metabolites with antifungal activity. The highest growth inhibition of A. carbonarius was obtained by cultivating L. plantarum MZ809351 (LAB 31) in the presence of xylitol and glycerol. Under these conditions, in addition to 9-octadecenoic acid, 3 diketopiperazines or cyclic dipeptides were identified, including cyclo (Leu-Leu), cyclo (Pro-Gly) and cyclo (Val-Phe), these compounds have been related to microbial antifungal activity. On the other hand, adding xylitol and glycerol to the MRS broth reduced the Ochratoxin A (OTA) content to 56.8 and 54.7%, respectively. This study shows the potential for using L. plantarum as a biocontrol agent.; La pérdida de alimentos causada por la contaminación de microorganismos es una problemática importante para atender la demanda creciente de la población humana. Específicamente la contaminación por hongos es un tema de interés puesto que producen micotoxinas a las que se les atribuye diversas enfermedades. Para resolver la problemática antes mencionada se propone el uso de bacterias ácido lácticas (BAL) como antagonistas del crecimiento del hongo Aspergillus carbonarius. En el trabajo se busca potenciar el efecto antifúngico de cepas de BAL mediante la modificación de la formulación del medio de cultivo, así como identificar metabolitos con actividad antifúngica. En una primera etapa se realizó un análisis de los productos de fermentación de las BAL. Se encontró que son homofermentativas, por producir principalmente ácido láctico con bajas concentraciones de ácido propiónico, etanol y en el caso de la cepa BAL 31 también se produjo ácido butírico. Se determinó que la mayor actividad antifúngica se presentó cuando el sobrenadante libre de células fue obtenido entre las 72 y 96 h de cultivo de las BAL bajo condiciones anaerobias. En una segunda fase se evaluó la actividad antifúngica cuando se modifican la cantidad de fuente de nitrógeno y algunos factores nutricionales. Se encontró que la BAL 7 de México y la BAL 31 de Costa de Marfil son las que presentan mayor actividad antifúngica, también se encontró que tanto el extracto de levadura y citrato de amonio pueden ser eliminados del medio de cultivo sin afectar el crecimiento y la actividad antifúngica. Por último, el cloruro de calcio tiene un efecto negativo en la inhibición y el cloruro de sodio no tiene ningún efecto sobre la inhibición. La última sección corresponde al estudio del efecto de la adición de polioles al medio de cultivo MRS sobre la producción de metabolitos con actividad antifúngica. La mayor inhibición del crecimiento de A. carbonarius se obtuvo cultivando L. plantarum MZ809351 en presencia de xilitol y glicerol. En estas condiciones, además del ácido 9-octadecenoico, se identificaron 3 dicetopiperazinas o dipéptidos cíclicos, entre ellos ciclo (Leu-Leu), ciclo (Pro-Gly) y ciclo (Val-Phe), compuestos que han sido relacionados con actividad antifúngica. Por otro lado, la adición de xilitol y glicerol al caldo MRS redujo el contenido de ocratoxina A (OTA) a 56.8 y 54.7%, respectivamente. Este estudio muestra el potencial para usar L. plantarum MZ809351 como agente de biocontrol.